DESCRIPTION OF STRESS LEVELS AND MENSTRUAL DISORDERS IN D3 NURSING STUDENTS IN SIDOARJO - Risda Aprilia; Alfi Maziyah (Global Ten Public Health and Nursing Journal, 2023)
Health is very important for every human being, because without good health, every human being will find it difficult to carry out daily activities. Many problems will arise due to neglecting reproductive health, one of which can cause menstrual disorders. Menstrual disorders can be in the form of polymenorrhea, oligomenorrhea, amonerrhea, dysminorhea, and hypermenorhea. This research design used "Descriptive" Cross Sectional approach. This study aims to describe the level of stress and menstrual disorders in D3 Nursing Sidoarjo students. The results of the study on 123 respondents showed the stress level of D3 Nursing Sidoarjo students almost half did not experience disorders (normal) as many as 54 students (44%) the rest experienced stress which was divided into mild stress, moderate stress, severe stress, and very severe stress. Menstrual disorders in D3 Nursing Sidoarjo students who experienced amenorahae events as many as 4 students (6%), polimenorrhea events as many as 16 students (23%), oligomenorrhea events as many as 10 students (14%), dysminorrhea events as many as 12 students (17%), hypermenorrhea as many as 2 students (3%). From the results of the study it can be concluded that the level of stress in female students of D3 Nursing Sidoarjo almost half of the 123 respondents did not experience stress (normal) as many as 54 female students (44%). And menstrual disorders in D3 Nursing Sidoarjo students are most numerous.